Correlation Analysis between Mechanical Structure Design and Manufacturing Technology of NC Machine Tools - Liang, Chunlei (Journal of Theory and Practice of Engineering Science, 2023)
In the course of rapid economic development of modern society, our manufacturing industry has been given a chance to develop rapidly, which is closely related to the acceleration of the industrialization process and the support of science and technology. During the development of Chinese manufacturing industry, numerical control machine tool mechanical structure design and manufacturing technology as the key technology, to a great extent supported and promoted the progress and development of our country manufacturing industry. This article mainly based on the practice content, the analysis of the numerical control machine tool mechanical structure design and manufacturing technology correlation, expect for our country numerical control machine tool and even manufacturing industry development to provide important support.